1999
DOI: 10.1097/00005373-199911000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Pilon Fractures: A Comparison of Treatment Methods

Abstract: External fixation offers advantages in the treatment of the soft-tissue injury associated with pilon fractures, but malunion continues to be a problem with this method of fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
2
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 18 publications
2
120
2
6
Order By: Relevance
“…For the external fixation group, no two-staged protocol was undertaken in this study and external fixation was always a definitive device. Similar to many other authors, we found that definitive external fixation provided more malunion, stiffness or pain than ORIF [6,8,10]. Thus, we believe that external fixation should be preferentially used in two-staged protocols as a temporary device before ORIF or limited internal fixation [1,5].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For the external fixation group, no two-staged protocol was undertaken in this study and external fixation was always a definitive device. Similar to many other authors, we found that definitive external fixation provided more malunion, stiffness or pain than ORIF [6,8,10]. Thus, we believe that external fixation should be preferentially used in two-staged protocols as a temporary device before ORIF or limited internal fixation [1,5].…”
Section: Discussionsupporting
confidence: 87%
“…Many osteosynthesis techniques can be used for these fractures such as; traditional open reduction and internal fixation (ORIF), external fixation with or without limited internal fixation, intramedullary nailing or, more recently, minimally invasive plate osteosynthesis (MIPO) [5][6][7][8][9]. All of these techniques have advantages and disadvantages and there is no consensus concerning the management of these fractures [2,10].…”
Section: Introductionmentioning
confidence: 99%
“…22 Pugh et al studied outcome using an ankle spanning unilateral frame, an ankle sparing ring hybrid fixator and ORIF in fractures of tibial plafond finding no difference in rate of complications and union in the three groups. 23 Bone et al concluded that cross ankle fixators which completely immobilize the ankle joint have not been detrimental to patient. 7 In our study, functional range of ankle movement was maintained in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed its ability to serve as a concise and reliable communication tool in a research capacity [37]. In a similar fashion, the Tscherne system serves as an effective guide for predicting treatment and prognosis [6,7,9,12,22,30,38]. This has important implications in fracture care, where factors such as polytrauma and severe soft tissue injury may preclude primary definitive fixation.…”
Section: Purposementioning
confidence: 99%